(untitled) (Journal of Contemporary Philology, 2023)
The purpose of this paperis to show that there is an essential connection between Rules of Art, Pierre Bourdieu’s main work on literature, and his critique of neo liberalism, presented in his later works. Namely, starting from the Postscript at the end of Rules of Art, I show that the autonomy of the literary field obtained in the XIX century (with all its implications: the charismatic “celebration” of the author, the fetishization of literary works, the establishment of the anti-economic logic of literature and symbolic capital, the establishment of an “aesthetic gaze”, etc.) does not guarantee that the field will remain autonomous forever. In the first section of the paper, I present and analyze Pierre Bourdieu’s critique of the politics and economy of neoliberalism, particularly emphasising the consequences on the autonomy of literature and other cultural fields. Following Bourdieu, I argue that the only way to understand the autonomy of the literary field, in particular, and the autonomy of literature, in general, is to place them in this context of neoliberal politics and economics. In the second and main section, I present Pierre Bourdieu’s notion of “double historicization” as a method through which he tries to respond to the challenges that neoliberalism poses to culture and literature. I present a detailed analysis of this concept, which Bourdieu sets up as an alternative to both “internal” and “external readings”. In both cases – both in the first and in the second section – I emphasize his theoretical similarities with certain lines of thought of Anglo-American Marxism (Raymond Williams, Terry Eagleton, Frederic Jamieson) and some other theorists, such as Walter Benjamin and Jacques Rancière. Finally, I summarize the objectives of Rules of Art in three points viewed in this wider context.